Incidence of convulsive epilepsy in a rural area in Kenya. Issue 8 (10th June 2013) - Ngugi, Anthony K.; Bottomley, Christian; Scott, J. Anthony G.; Mung'ala–Odera, Victor; Bauni, Evasius; Sander, Josemir W.; Kleinschmidt, Immo; Newton, Charles R.
Summary Purpose There are only a few studies of incidence of epilepsy in low and middle income countries (LMICs). These are often small and conducted in specific age groups or areas where the prevalence of risk factors is high; therefore, these studies are not representative of the wider populations. We determined the incidence of convulsive epilepsy (CE) in a large rural population in Kenya. Methods We conducted two cross‐sectional surveys 5 years apart within a health and demographic surveillance system. Initially we identified residents without epilepsy who were then reexamined in the follow‐up survey to determine incidence. We estimated the overall incidence of CE and incidence by age‐group, sex, and by administrative location. Estimates were adjusted for attrition during case identification and for the sensitivity of the screening method. Key Findings In a cohort of 151, 408 people, 194 developed CE over the 5 years. The minimum crude incidence rate was 37.6/100, 000 persons per year (95% confidence interval (CI) 32.7–43.3) and adjusted for loss to follow‐up, and the sensitivity of the survey methodology was 77.0/100, 000 persons per year (95% CI 67.7–87.4). Incidence was highest in children 6–12 years (96.1/100, 000 persons per year; 95% CI 78.4–117.9), and was lowest in the 29–49 year age group (37.4/100, 000 persons per year; 95% CI 25.7–54.7). Significance We estimated a high incidence of convulsive epilepsy in this population. Incidence was highest early and late in life, suggesting that preventive interventions should target exposures that occur in these age groups. Incidence of focal epilepsy was more than twice that of generalized epilepsy, suggesting that etiologies that are amenable to intervention were most important in this population. It is likely that incidence is underestimated because of the early mortality of incident cases.